Rituals of Containment: Many Pandemics, Body Politics, and Social Dramas During COVID-19 in Pakistan - Ali, Inayat (Frontiers in Sociology, 2021)
Infecting millions of people, causing around 2 million deaths, and affecting billions of people worldwide, the coronavirus (COVID-19) pandemic is not merely one pandemic but many. These many pandemics, which I identify herein, have revealed the overt and subtle entanglements among religion, science, and politics around COVID-19. Building on my current ethnographic research on COVID-19 (C-19) using purposive sampling and interview guide in Pakistan, and borrowing from various anthropological concepts such as Victor Turner’s “social drama” and ritual I have developed a concept that I call rituals of containment. With this concept, I extend my previous argument regarding “symbolic ownership” to show a visible “body politics” by demonstrating how religion, science, and politics around COVID are entangled at individual and government levels. This has become observable through the Pakistani government's rituals of containment to deal with COVID-19. Such entanglements are visible in the case of strategies to tackle infected “viral bodies,” as the government has enacted its authority: (1) to bury what I am terming the dead viral body without its beloved ones present; (2) to return or not to return this body to family members in a coffin; (3) or to provide the grieving family with a symbolic empty coffin. These Covidian politics have led to the question: Who in actuality owns the body? In conclusion, I argue that the problem lies in the discriminatory and contradictory government’s rituals of containment, not in using scientific evidence and guidelines.